Let-7i-5p promotes a malignant phenotype in nasopharyngeal carcinoma via inhibiting tumor-suppressive autophagy. (10th April 2022) - You, Bo; Zhang, Panpan; Gu, Miao; Yin, Haimeng; Fan, Yue; Yao, Hui; Pan, Si; Xie, Haijing; Cheng, Tianyi; Liu, Huiting; You, Yiwen; Liu, Jisheng
Abstract: MicroRNAs (miRNAs) regulate gene expression to participate in carcinogenesis and tumor progression. Therefore, identification of a malignant phenotype associated with miRNAs and therapeutic targets will contribute substantially in improving nasopharyngeal carcinoma (NPC) treatment. In this study, we demonstrated that overexpression of let-7i-5p promotes the malignant phenotype by acting as an autophagy suppressor by targeting ATG10 and ATG16L1 in NPC. Expression levels of let-7i-5p were markedly increased in NPC and head and neck cancers based on an analysis of the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases. Using a cohort comprising 150 NPC tissues, we found that let-7i-5p was correlated with advanced stage, recurrence, metastasis, lymph node metastasis, and poor clinical outcomes. In addition to a series of in vitro cellular analyses, in vivo mouse tumor models revealed that let-7i-5p inhibits autophagy and promotes the malignant phenotype of NPC by targeting ATG10 and ATG16L1. Our findings demonstrate that let-7i-5p may represent a promising therapeutic target for NPC treatment. Highlights: Let-7i-5p overexpression may predict advanced stage, recurrence, metastasis, and poor clinical outcomes in NPC. Overexpression of let-7i-5p strongly accelerates the NPC malignant phenotype and inhibits autophagy. ATG10 and ATG16L are two novel target genes of let-7i-5p in NPC cells. ATG10 and ATG16L1 are essential for the promotion of malignant NPC phenotypes by let-7i-5p.